The Philosophical Problems Surrounding Interpersonal Utility Comparisons - Kwarciński, Tomasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
I attempt a systematic analysis of the philosophical problems related to interpersonal utility comparisons. The issue has importance both for economics theory and practice. There are four groups of such problems: semantic, epistemological, anthropological and axiological. My investigation of intergroup relationships led to the following conclusions: first, the most important problems are semantic ones; second, descriptive interpretations of interpersonal utility comparisons are based on doubtful semantic and epistemological premises; third, normative interpretations of interpersonal utility comparisons can be formulated upon different epistemological premises.